Ocean Acidification Experiments in Large-Scale Mesocosms Reveal Similar Dynamics of Dissolved Organic Matter Production and Biotransformation - Zark, Maren; Broda, Nadine K.; Hornick, Thomas; Grossart, Hans-Peter; Riebesell, Ulf; Dittmar, Thorsten (Frontiers in Marine Science, 2017)
Dissolved organic matter (DOM) represents a major reservoir of carbon in the oceans. Environmental stressors such as ocean acidification (OA) potentially affect DOM production and degradation processes, e.g. phytoplankton exudation or microbial uptake and biotransformation of molecules. Resulting changes in carbon storage capacity of the ocean, thus, may cause feedbacks on the global carbon cycle. Previous experiments studying OA effects on the DOM pool under natural conditions, however, were mostly conducted in temperate and coastal eutrophic areas. Here, we report on OA effects on the existing and newly produced DOM pool during an experiment in the subtropical North Atlantic Ocean at the Canary Islands during an (1) oligotrophic phase and (2) after simulated deep water upwelling. The last is a frequently occurring event in this region controlling nutrient and phytoplankton dynamics. We manipulated nine large-scale mesocosms with a gradient of pCO2 ranging from ~350 up to ~1030 µatm and monitored the DOM molecular composition using ultrahigh-resolution mass spectrometry via Fourier-transform ion cyclotron resonance mass spectrometry (FT-ICR-MS). An increase of 37 µmol L-1 DOC was observed in all mesocosms during a phytoplankton bloom induced by simulated upwelling. Indications for enhanced DOC accumulation under elevated CO2 became apparent during a phase of nutrient recycling towards the end of the experiment. The production of DOM was reflected in changes of the molecular DOM composition. Out of the 7,212 molecular formulae, which were detected throughout the experiment, ~50% correlated significantly in mass spectrometric signal intensity with cumulative bacterial protein production and are likely a product of microbial transformation. However, no differences in the produced compounds were found with respect to CO2 levels. Comparing the results of this experiment with a comparable OA experiment in the Swedish Gullmar Fjord, reveals similar succession patterns for individual compound pools during a phytoplankton bloom and subsequent accumulation of these compounds were observed. The similar behavior of DOM production and biotransformation during and following a phytoplankton bloom irrespective of plankton community composition and CO2 treatment provides novel insights into general dynamics of the marine DOM pool.